Analisis Konsepsi Toleran dalam Buku Teks Hadis Kelas XI Keagamaan Madrasah Aliyah - Abu Amar (Cendekia, 2023)
The background of this study is the lack of articles discussing the value of tolerance in the Madrasah Aliyah Religious Specialization Textbook. This study aims to describe the suitability of competencies and learning objectives and analyze the target object of tolerance through the Rainer Forst perspective in the Hadith Class XI Textbook of Madrasah Aliyah Religious Specialization. As a literature study with and applying content analysis, it is concluded that competency development and tolerance learning objectives are in accordance with the curriculum. Development of learning materials through studies of word meanings, translations, quality, suitability of hadiths and verses of the Qur'an, and analysis of hadith content. The target objects of tolerance consist of waliyyul 'amr, Aswaja scholars, and Experts of the Bait they must be obeyed absolutely and are allowed to dominate other human beings on the basis of maslahah and madlarat considerations. Limited tolerance for dealing with social, cultural, and worldly issues, no tolerance for matters of faith or belief. Through Rainer Forst's conception of tolerance, the tolerance strata of fellow Muslims include permission, coexistence, respect, and esteem, while tolerance with non-Muslims is limited to the permission and coexistence strata. It is not possible to achieve respect and esteem strata